Al-Akhtā’ al-Śarfiyyah fī al-Rasā’il al-Jami’iyyah li Marḥalah al-Bakālūrīs fī al-Jāmi’ah - Rohmatin, Yuani (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to analyze Arabic morphological errors in undergraduate-level written work at IAIN Ponorogo. This research is qualitative because of the type of data collected in words and behavior and the data obtained by the document Analysis. Researchers use the data analysis model Miles and Huberman. The results of the study are: 1) There are errors in nouns consisting of ma'rifah nakirah on pronouns, there are eight errors; in the word point, there are two errors; the conjunction, there are four errors, and the word is based on the ma'rifah there are six errors, and the error on single, double and plural form there is one error. 2) Error in verbs: Seven errors consist of verbs of the past form. There are two errors; the verb is or will come with five errors. 3) Errors on the hamzah: 14 errors are included in the hamzah. At the beginning of the word, there are 13 errors; hamzah, amid the word, there is one error.